The Meaning Of Abogean Religiosity In The Perspective Of The Knowledge Sociology Karl Manheim (Case Study In The Kencong Area Of Jember) - Bahrudin, Bahrudin; win usuluddin; Moh. Dahlan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
In carrying out their worship practices, the Aboge are different from the general public: Wudu repeated three times, wirid khususiyah, qunut in every obligatory prayer and other practices. It is done in order to get closer to the creator. based on the ancestral beliefs of the Aboge itself. The methodology is qualitative, Filey Research type, philosophical and phenomenological research approach, Data collection techniques (Observation, Documentation and Interview). and Data analysis uses content analysis which tries to interpret Aboge in the perspective of philosophy and sociology. The results of the study are the Aboge people in the Kencong Jember area which in practice they adopt many of the teachings used by their ancestors. The practices that are done are: Self purification by repeating bathing and ablution with a number of 3 times to 5 times, Bedug which is beaten as a sign of prayer, Qunut which is done both for the five daily prayers and Sunnah, and Wirid Aboge which is done with two stages. The meanings they give in each practice are: Purity, Blessing, Prayer, Medicine/Syifak, and Cultural Heritage. Factors that influence the meaning of knowledge and teachings from their ancestors.